2021
DOI: 10.1371/journal.pone.0258646
|View full text |Cite
|
Sign up to set email alerts
|

Return of individual research results from genomic research: A systematic review of stakeholder perspectives

Abstract: Despite the plethora of empirical studies conducted to date, debate continues about whether and to what extent results should be returned to participants of genomic research. We aimed to systematically review the empirical literature exploring stakeholders’ perspectives on return of individual research results (IRR) from genomic research. We examined preferences for receiving or willingness to return IRR, and experiences with either receiving or returning them. The systematic searches were conducted across fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 219 publications
(667 reference statements)
2
29
0
Order By: Relevance
“…Reasons for declining IFs or secondary findings include a lack of understanding, worry of increased psychological burden, and fear of insurance discrimination (Anderson et al, 2017;Mackley et al, 2018). However, individuals who decline IFs remain a minority and this is consistent in both the clinical and research settings, although the boundary between these two contexts is blurring in translational genomics (Vears et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for declining IFs or secondary findings include a lack of understanding, worry of increased psychological burden, and fear of insurance discrimination (Anderson et al, 2017;Mackley et al, 2018). However, individuals who decline IFs remain a minority and this is consistent in both the clinical and research settings, although the boundary between these two contexts is blurring in translational genomics (Vears et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…13,14,[24][25][26][27] This work, however, is sparse compared with the volume of studies generated within United States and limited in its extension of the geographical and cultural reach of research. 19 Our findings suggest that these limitations have implications for genomics policy, both in the formal development of international standards and guidance, and in the extent to which pioneer initiatives function as informal exemplars of best practice.…”
Section: Discussionmentioning
confidence: 87%
“…16,18 However, this discourse has mostly involved researchers, policy makers, and public audiences from the United States, and thus, it cannot be assumed that it will naturally translate to global contexts outside the United States. 19 The differences in policy and normative positions on RoR around the world reflects differing cultural views about participant needs, different national health care systems, and the constraints of research sector resources in different contexts. 5 To date, however, there is little evidence on how public perceptions of the desirability of RoR-and their ability to motivate participation-vary across such contexts and internationally.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, this article is different (in very important ways) from other studies, which, for example, have demonstrated how institutions have a duty to support return as a form of ancillary care or additional foreseeable service in research, exploring this duty by appealing mostly to norms and principles dominant in the Global North 13. The study is also different from other descriptive studies14 15 that report participants’ views on cost-related challenges around feeding back findings in genomic research and opinions about how to address the same. This study is also different from non-descriptive studies16–18 that aim to develop a decision flow chart and/or suggest principles that researchers can draw on to manage incidental findings.…”
Section: Introductionmentioning
confidence: 74%